Implementasi Sistem Informasi Penjualan Kue Menggunakan Framework Codeigniter Dengan Pendekatan Metode Prototype - Aulianita, Rizki; Mukhayaroh, Anna (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management; Vol 9 No 2 (2024): INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS (DESEMBER 2024), 2024)
This research is motivated by the need for cake business owners to efficiently manage sales and ordering transactions. Manual systems often lead to data inaccuracies and lengthy processing times, necessitating a technology-based solution. This study aims to develop a web-based cake sales information system using the CodeIgniter framework and the prototype method. This method allows researchers to interact directly with users, gather feedback, and refine the system according to evolving needs. The data used includes sales transaction data, cake orders, and product information from cake business owners. System development involves several stages, including requirements analysis, system design, implementation, and testing based on user input. The results of this research indicate that the web-based cake sales information system improves the efficiency of the sales process, minimizes recording errors, and facilitates information access for users. In conclusion, this system is effective in supporting cake sales management and can be relied upon to expedite customer service.